Intestinal-type adenocarcinoma presenting as a mandibular mass: An unusual presentation - Nouman Rashid; Adity Bansal; Ashi Chug (Wolters Kluwer Medknow Publications, 2021)
Intestinal-type adenocarcinoma is an aggressive malignancy with the rare possibility of metastatic spread to the mandible. We represent a case of a 30-year-old female patient who reported with a chief complaint of a right mandibular mass for 4 months. Orthopantomogram X-ray observed an ill-defined lytic lesion with severe periosteal reaction. Incisional biopsy revealed "colonic variant of intestinal-type adenocarcinoma." Expression of cytokeratin 20 and caudal type homeobox transcription factor 2 (CDX-2) markers was seen on immunohistochemistry. Biochemical markers such as serum cancer antigen 125, serum alkaline phosphatase, and serum carcinoembryonic antigen were raised. Contrast-enhanced computed tomography of the thorax and abdomen suggested cavitary lesions in the bilateral lungs, right adrenal gland, and mediastinum. Positron emission tomography revealed multiple lesions in the body, hence confirming the diagnosis. The patient was kept on palliative chemotherapy. It is concluded that prompt diagnosis and initiation of treatment increases the chances of survival in such cases.